Analisis Self-Defence pada Mahasiswa Korban Bullying dan Implikasinya dalam Pelayanan Konseling - Febriska, Dian; Nurfarhanah, Nurfarhanah (TSAQOFAH, 2025)
Bullying is a deliberate and repeated act of oppression by an individual or group with greater power against a weaker party, with serious impacts on the victim’s psychological condition. This study aims to identify the types of self-defence mechanisms currently employed by victims of bullying. A qualitative approach with a case study method was used, involving two female students from Universitas Negeri Padang as the main subjects, with additional informants including parents and close friends. Data were collected through in-depth interviews, observation, and documentation, and analyzed thematically. The results show that both subjects employed various self-defence mechanisms, including both adaptive and maladaptive types. Identified mechanisms include acting out, isolation, splitting, rationalization, dissociation, somatization, displacement, humor, sublimation, anticipation, altruism, and suppression. These patterns reflect the subjects’ efforts to cope with psychological pressure resulting from bullying experiences, with variations in responses influenced by the intensity of the events, social support, and individual characteristics. The findings underscore the importance of understanding self-defence mechanisms in counseling practice to assist bullying victims in developing more adaptive coping strategies and supporting their long-term emotional recovery process.